If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(r + b) = 0 Reorder the terms: -4(b + r) = 0 (b * -4 + r * -4) = 0 (-4b + -4r) = 0 Solving -4b + -4r = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4r' to each side of the equation. -4b + -4r + 4r = 0 + 4r Combine like terms: -4r + 4r = 0 -4b + 0 = 0 + 4r -4b = 0 + 4r Remove the zero: -4b = 4r Divide each side by '-4'. b = -1r Simplifying b = -1r
| -6-(-20)+(-19)-19= | | 7/2r-8=15/r-10 | | 3.5k=39-2(3) | | -2x+-2z= | | -3=4(4(-3))+45 | | (47-2x)(23-2x)=595 | | 3/5k=39-2(3) | | -36+12=24 | | (12b+7)(5b-15)=0 | | Cos(x)+sen(x)=0 | | x+x+24+2(x+24)=376 | | 4(d-7)=2(3x)+6 | | N+4=(3)-n | | x-14=194 | | -11+10(3)=2c | | -7.8+4.8=7x-8.9-6x | | -11+10r=2c | | 4(6+3)+2(1+2)= | | a/b=7/18 | | 9.5+0.25x=9.5 | | (3x/3)^2x | | 935+0.25x=9.5 | | -14x+70= | | X-39+x+6=180 | | x-a=m | | x+24+3x-17-3x-22= | | x+10-y=4198 | | W/25-790=1400 | | 4b(6-7b)=2c | | 3(-1+5x)=-18 | | 4d-1=d+8 | | 10x^4-63x^3+52x^2+63x+10=0 |